2019
DOI: 10.3390/ijms20092205
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Hematuria: Cause or Consequence of Renal Inflammation?

Abstract: Glomerular hematuria is a cardinal symptom of renal disease. Glomerular hematuria may be classified as microhematuria or macrohematuria according to the number of red blood cells in urine. Recent evidence suggests a pathological role of persistent glomerular microhematuria in the progression of renal disease. Moreover, gross hematuria, or macrohematuria, promotes acute kidney injury (AKI), with subsequent impairment of renal function in a high proportion of patients. In this pathological context, hemoglobin, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 87 publications
2
45
0
Order By: Relevance
“…For example, in-hospital AKI is associated with proteinuria, and this relationship increases with severity of AKI, possibly leading to CKD [23,24]. Hematuria was also reported to be associated with AKI, both as a possible cause through tubular obstruction and heme pigment-induced kidney injury as well as a consequence of AKI due to renal inflammation [25,26]. Data on the prevalence, risk, and associated outcomes related to proteinuria and hematuria in patients with COVID-19 are more limited.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…For example, in-hospital AKI is associated with proteinuria, and this relationship increases with severity of AKI, possibly leading to CKD [23,24]. Hematuria was also reported to be associated with AKI, both as a possible cause through tubular obstruction and heme pigment-induced kidney injury as well as a consequence of AKI due to renal inflammation [25,26]. Data on the prevalence, risk, and associated outcomes related to proteinuria and hematuria in patients with COVID-19 are more limited.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Along the same lines, we recently observed that up to 25% of IgA nephropathy patients with haematuria-associated AKI do not recover baseline renal function, suggesting long term negative effects [12]. The deleterious effects of haematuria include direct tubular damage by intratubular obstruction by red blood cell casts, toxic effects of haemoglobin (Hb) and haem on kidney epithelial cells, and erythrophagocytosis by renal tubular cells [13]. In tubular cells, Hb induces oxidative stress, cell death, and pro-inflammatory and pro-fibrotic responses [13].…”
Section: Introductionmentioning
confidence: 92%
“…The deleterious effects of haematuria include direct tubular damage by intratubular obstruction by red blood cell casts, toxic effects of haemoglobin (Hb) and haem on kidney epithelial cells, and erythrophagocytosis by renal tubular cells [13]. In tubular cells, Hb induces oxidative stress, cell death, and pro-inflammatory and pro-fibrotic responses [13].…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue covers research articles that investigated the molecular mechanisms of inflammation [1][2][3] and injury [4,5] during different renal pathologies and renal regeneration [6], diagnostics using new biomarkers [7][8][9], and the effects of different stimuli like medication or bacterial components on isolated renal cells or in vivo models [10][11][12], all of which were summarized in a very simplified manner. Furthermore, this Special Issue contains important reviews that dealt with the current knowledge of cell death and regeneration [13,14], inflammation [15][16][17][18], and the molecular mechanisms of kidney diseases [19][20][21][22]. In addition, the potential of cell-based therapy approaches that use mesenchymal stromal/stem cells (MSCs) or their derivates is summarized [23][24][25].…”
mentioning
confidence: 99%
“…MSCs predominantly act through secreted factors, including microRNAs that are contained within extracellular vesicles, cytoprotective effects anti-inflammatory effects, anti-apoptotic effects, and the suppression of oxidative stress. In addition, further reviews summarized the inflammation-mediated mechanisms or the inflammasome in various renal diseases [15][16][17][18]26,27]. Very interesting and new approaches shed a light on the role of non-coding RNAs, either in the progression of glomerular or tubulointerstitial kidney diseases [20] or as new therapeutic targets or biomarkers for fibrotic changes [29].…”
mentioning
confidence: 99%